Pengembangan LKPD Berbasis Model Pembelajaran Problem Based Learning (PBL) Terintegrasi Nilai-Nilai Islam - Darojah, Auzi Ulfah Husnud; Vahlia, Ira; Anwar, Rahmad Bustanul (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
Abstract This study is to detail the creation of Student Worksheets (LKPD) that incorporate Islamic principles into the System of Linear Equations in Two Variables (SPLDV) curriculum and are based on the Problem Based Learning (PBL) learning model. The ADDIE model is used in this study. Experts in materials, design, and Islamic principles participated in the product validation questionnaires used to gather data for the study, which was carried out at MTs Muhammadiyah Metro Lampung. Additionally, students were involved through the implementation of a product practicality questionnaire. Ten students worked in a small group to complete the practicality test. By following the ADDIE steps—analysis stage, which includes study of teaching materials and student characteristics—the research development's outcomes are PBL-based LKPD integrated with Islamic principles in SPLDV material. design stage, which encompasses learning planning; development stage, wherein instructional materials are adjusted in response to expert input: Following the implementation stage, which is conducted through small group trials, the evaluation stage is conducted at each level. Very valid percentages of 89.5%, 85.7%, and 88% were reached by material experts, design experts, and Islamic values experts, respectively, for their validation results. An evaluation of the educator response questionnaire's practicality yielded an 87.2% extremely practical proportion. Class VIII SPLDV material is legitimate and beneficial for the educational process, and LKPD was founded with an integrated PBL learning model with Islamic principles based on the research findings.